O papel do direito na agricultura como propulsora da segurança alimentar no Brasil - Oliveira, Sócrates Costa (2023)
This research addresses the lack of access to adequate food in Brazil, affecting more than half of the population, particularly women and rural residents. The Food and Agriculture Organization (FAO) is already directing studies towards identifying new food that have greater harmony with the environment, including algae. The potential of algae in nutrition is considerable, primarily due to their nutritional properties and being an ecologically viable food source. The cultivation of seaweed (algiculture) and its consumption can benefit communities along the Brazilian coastline, incorporating it as both food and income through family farming, within the context of the Blue Economy. It is crucial to devise legal frameworks that favor food security and ensure that algiculture benefits both Brazilian coastal communities and environmentally harmonious production. Given the importance of ensuring food security allied with environmental preservation, the research problem emerges: how can the law facilitate the development of algiculture to promote more sustainable food security in Brazil? The overall objective is to understand how the law can play a leading role in implementing ecologically appropriate public policies and food production practices, promoting food and nutritional security while respecting environmental balance. Regarding methodology, this study employs a qualitative and exploratory approach, utilizing deductive methods through bibliographic and documentary source research, including specific legislation, official documents, and related organizations. The conclusion is that the law should focus on ensuring the integration of communities with food production methods harmonious with the environment to promote self- consumption, production commercialization, and income generation. In this regard, algiculture can be an example of a viable production method. It is crucial to maintain continuous and ecological production, aiming for the perpetuation of algae species in natural banks and their ecosystem. Therefore, the application of principles and guidelines from the Ecosystem Approach to algiculture can favor food security for coastal communities and environmental protection.